Effects of Fosetyl-Al, a fungicide on meiosis of Lycopersicon esculentum Mill. - Çali, Ilkay Özturk; Kesercioglu, Teoman (Bangladesh Journal of Botany, 2011)
Effects of Fosetyl-Al (80% Aliette WG 800), widely applied on tomato plants (Lycopersicon esculentum Mill.) grown in greenhouse against Phytophthora infestans revealed that at recommended dosage (200 g/100 l water) and the double dosage (400 g/100 l water), the fungicide causes various anomalies in pollen meiosis. Key words: Fosetyl-A;, Fungicide; Lycopersicon esculentum; Meiosis; Pollens DOI: 10.3329/bjb.v39i2.7486 Bangladesh J. Bot. 39(2): 237-240, 2010 (December)